Spreminjanje prometne rabe zemljišč v Sloveniji - Bole, David (Georitem, 2015)
It is clear that different types of the population's mobility have an impact on the transportation land use and thereby shape our living environment. According to the land cadastre data Slovenia has 465 km2 of transportation land use, which represents more than 2 % of the country's surface. The transportation land use areas are expanding in the last decade, although slower than other built-up areas. The transportation land use analysis on the state level indicates those areas of Slovenia, where the level of transportation land use has risen the most. These are areas with a new transportation infrastructure (roads, railroads), tourist and some other (sub)urbanized areas. The results have shown that local political and planning decision-making represents an important factor in the increase of the transportation land use in Slovene towns.